Identifying the sources of firms' institutional entrepreneurship capability: the influence of firms on recent changes in brazilian electricity sector´s norms and regulations - Oliveira, Leonardo Augusto dos Santos (2017)
Our research draws on the Institutional Entrepreneurship Capability (DiMaggio, 1988) intending to uncover the sources of institutional entrepreneurship capabilities and if these capabilities developed at home can be used by overseas subsidiaries to deal with local institutions. Scholars have focused on describing Institutional Entrepreneurship, not analyzing it, assuming agency exists; they have failed to explain how actors overcome the institutional environment in which they are embedded to be able to alter it (Mutch, 2007). So far, we have not been able to find any research that has specifically defined and put together the organization´s characteristics providing the ability to influence and change institutions. This paper contributes to the Institutional Entrepreneurship literature by filling this gap. We first identify which specific resources are providing companies with institutional entrepreneurship capability, providing us with a framework for measuring the ability to influence and change institutions. We identify four dimensions of institutional entrepreneurship capability: Political Power; Technological Power; Social Power; and Financial Power. We further developed Hypotheses about which of these sources of institutional entrepreneurship capabilities can be transferred from headquarters to overseas subsidiaries, thus, contributing to international business literature by introducing the institutional entrepreneurship capability, of both headquarters and subsidiaries, on subsidiaries' analysis. We further develop a measurement model for Institutional Entrepreneurship Capability (IEC), determining the degree of its presence in firms by disaggregating and describing IEC power dimensions to obtain a model to measure this capability. It assesses firm capability to change existing institutional arrangements. As there usually exist several institutional entrepreneurs in any field, measuring their IEC is relevant to understand the field, and how institutional change takes place, considering firm-specific capabilities. Intending to bridge the gap between abstract theoretical constructs and empirical measures, we define IEC through a network of associations with its observable properties and proxies, determining possible measurement techniques. This study concerns the recent changes in the Brazilian energy sector, which resulted in a set of new rules and regulations for the production and distribution of electrical energy in the national territory. We have analyzed all public hearings ranging from 2010 to 2015 at the National Agency for Electrical Energy (ANEEL) that resulted in changes the regulatory framework. About this period, we have identified 86 public hearings, with the participation of 217 entities, including state-owned and private companies, associations and state and federal governmental entities and individual contributions. About these 86 public hearings, we have identified 625 participations totaling 3170 contributions. Results showed the proposed model for measuring Institutional Entrepreneurship Capability of firms had a good fit and that this construct explained 56% of the variance in Firms´ driven institutional change. A theoretical contribution was made on the transferability of IEC from headquarters to subsidiaries oversee. We proposed further research.